Osing Tradition Preservation Learning Based on Customs: Case Study at Pesinauan Traditional School, Banyuwangi Regency Pembelajaran Pelestarian Tradisi Osing Berbasis Adat: Studi Kasus di Sekolah Adat Pesinauan, Kabupaten Banyuwangi - Kartika Efendi, Yuli; Hardika, Hardika; Ahmad, Ahmad; Zulkarnain, Zulkarnain; Sucipto, Sucipto; Redjeki, Endang Sri (Universitas Negeri Padang, 2025)
The Osing community, as one of the indigenous communities in Indonesia, has a unique and distinctive cultural wealth. In the era of globalization, the challenges in maintaining local cultural identity are increasingly complex. This article discusses efforts to build the next generation of Osing traditions through the approach of traditional schools and local cultural education. This study uses a case study method by focusing on educational practices in traditional schools in the Banyuwangi area, East Java. The results of the study indicate that traditional schools play an important role in internalizing Osing cultural values to the younger generation through a holistic and participatory approach. This article provides recommendations for strategies to strengthen local cultural education in order to maintain the sustainability of the Osing tradition